Rectracted: Anti-ribosomal-phosphoprotein autoantibodies penetrate to neuronal cells via neuronal growth associated protein, affecting neuronal cells in vitro. (6th May 2016) - Kivity, Shaye; Shoenfeld, Yehuda; Arango, Maria-Teresa; Cahill, Dolores J; O'Kane, Sara Louise; Zusev, Margalit; Slutsky, Inna; Harel-Meir, Michal; Chapman, Joab; Matthias, Torsten; Blank, Miri
Abstract: Objective: Anti-ribosomal-phosphoprotein antibodies (anti-Ribos.P Abs) are detected in 10–45% of NPSLE patients. Intracerebroventricular administration of anti-ribosomal-P Abs induces depression-like behaviour in mice. We aimed to discern the mechanism by which anti-Ribos.P Abs induce behavioural changes in mice. Methods: Anti-Ribos.P Abs were exposed to human and rat neuronal cell cultures, as well as to human umbilical vein endothelial cell cultures for a control. The cellular localization of anti-Ribo.P Abs was found by an immunofluorescent technique using a confocal microscope. Identification of the target molecules was undertaken using a cDNA library. Immunohistochemistry and an inhibition assay were carried out to confirm the identity of the target molecules. Neuronal cell proliferation was measured by bromodeoxyuridine, and Akt and Erk expression by immunoblot. Results: Human anti-Ribos.P Abs penetrated into human neuronal cells and rat hippocampal cell cultures in vitro, but not to endothelial cells as examined. Screening a high-content human cDNA-library with anti-Ribos.P Abs identified neuronal growth–associated protein (GAP43) as a target for anti-Ribos.P Abs. Ex vivo anti-Ribos.P Abs bind to mouse brain sections of hippocampus, dentate and amygdala. Anti-Ribos.P Abs brain-binding was prevented by GAP43 protein. Interestingly, GAP43 inhibited in a dose-dependent manner the anti-Ribos.P Abs binding to recombinant-ribosomal-P0, indicating mimicry between the ribosomal-P0 protein and GAP43. Furthermore, anti-Ribos.P Abs reduced neuronal cell proliferation activity in vitro (P < 0.001), whereas GAP43 decreased this inhibitory activity by a factor of 7.6. The last was related to Akt and Erk dephosphorylation. Conclusion: Anti-Ribos.P Abs penetrate neuronal cells in vitro by targeting GAP43. Anti -Ribos.P Abs inhibit neuronal-cell proliferation via inhibition of Akt and Erk. Our data contribute to deciphering the mechanism for anti-Ribos.P Abs' pathogenic activity in NPSLE.